Dose and Duration Fermentation (Passiflora edulis var. edulis) by Phanerochaete chrysosporium on The Physical and Chemical Feed Quality - Wahyu Cristine Pinem (Universitas Sumatera Utara, 2015)
The study aimed to examine the effect of passion fruit hulls flour fermented with Phanerochaete chrysosporium on the physical and chemical feed quality. Research conducted at the Laboratory of Animal Breeding and Reproduction, in June-July 2015. This research used a Factorial Completely Randomized Design (CRD). The treatment consisted of 2 factors : dose inokulum (104 CFU/g, 106 CFU/g) and fermentation duration (0;7;14 dan 21 days). Parameters studied were bulk density, compacted bulk density, specific gravity, crude protein and crude fiber content. The result showed that the factor of fermentation duration had significantly different (P<0,05) on the bulk density and the compacted bulk density. The factors dose and the day duration gives highly significantly different (P<0,01) on crude protein and crude fiber content. While the interaction between dose and fermentation duration is only found in a bulk density and crude protein content. The conclusion of this study that the best dose is 106 CFU/g with duration 14 days to ferment passion fruit hulls by Phanerochaete chrysosporium . Keywords : Passion Fruit Hulls, Dose, Duration of fermentation, Phanerochaete chrysosporium, Physical quality, Chemical quality.